From a Developing to an Emerging Economy: Côte d'Ivoire's Tax Policy Challenges - Perret, Sarah (OECD Taxation Working Papers, 2016)
Côte d'Ivoire aims at reaching emerging country status by 2020. However, Côte d'Ivoire's tax revenues are not sufficient to finance its growing needs for public investment in infrastructure, education and health. Tax policy is not just a question of resources-Côte d'Ivoire will also have to attempt to reform a tax system which distorts behaviour in many parts of the economy, which plays only a limited role in redistribution and inclusiveness, and lacks transparency. The authorities will have to prioritise a shift in the tax mix that gradually replaces the most distortive taxes, such as customs duties, with more neutral taxes; cast the tax net more widely to prevent that a limited number of taxpayers in the formal sector bear most of the tax burden; make the tax system simpler and more coherent; rationalise the many exemptions, especially in VAT, corporate tax and personal income tax; strengthen international tax rules to encourage multinationals to pay their fair share of taxes; increase the capacity of tax authorities; and enhance tax morale. Côte d'Ivoire cannot settle for partial reforms-it needs to phase in a comprehensive tax reform to meet its needs as an emerging economy